Towards Eco-Industrial Park in Malaysia: Promising Opportunities, Challenges and Regulator Roles - Zailan, Roziah; Fatimah Saad, Siti; Jamaluddin, Khairulnadzmi; Rafidah Wan Alwi, Sharifah; Jeng Shiun, Lim; Dian Tan, Yue; Nur Hidayah Mohamad, Siti; Lawal, Musa; Arif Misrol, Mohd; Steven Kuba, Nuhu; Nadzri Md Reba, Mohd; Ai Chin , Thoo; et al. (International Journal of Psychosocial Rehabilitation, 2020)
The progressive development of Eco-Industrial Park (EIP) in most Asian Developing Countries (ADC) has led Malaysia to show interest in EIPs development. The recent transition from the linear industrial park towards EIP is gaining attention in Malaysia due to the mutual benefits that can be achieved via material and utility sharing. The implementation of industrial symbiosis concept in EIP, however, depends on various attributes including law and regulation, finance, research and development, technology, environmental and so forth. Recently, new eco/green concepts industrial parks are upcoming in this country, however, it needs to meet with specified EIP characteristics. A systematic framework of EIP for Malaysia is required and yet to be developed. Prior to such a systematic approach, this paper reviews the current industrial park in Malaysia and presents the way forward transition into EIP. Promising opportunities and challenges of EIP in Malaysia have been thoroughly investigated and highlighted in this paper. Through the preliminary studies, the role of regulators mainly government and government institutions are prominent as a spur to adopt industrial ecology in the EIP development.